TRPs in Pain Sensation - Jardín, Isaac; López, José J.; Diez, Raquel; Sánchez-Collado, José; Cantonero, Carlos; Albarrán, Letizia; Woodard, Geoffrey E.; Redondo, Pedro C.; Salido, Ginés M.; Smani, Tarik; Rosado, Juan A. (Frontiers in Physiology, 2017)
According to the International Association for the Study of Pain (IASP) pain is characterized as an “unpleasant sensory and emotional experience associated with actual or potential tissue damage”. The TRP super-family, compressing up to 28 isoforms in mammals, mediates a myriad of physiological and pathophysiological processes, pain among them. TRP channel might be constituted by similar or different TRP subunits, which will result in the formation of homomeric or heteromeric channels with distinct properties and functions. In this review we will discuss about the function of TRPs in pain, focusing on TRP channles that participate in the transduction of noxious sensation, especially TRPV1 and TRPA1, their expression in nociceptors and their sensitivity to a large number of physical and chemical stimuli.